Syntactic and Semantic Rules in Old English Adjective Formation - Raquel Vea Escarza (Miscelánea: A Journal of English and American Studies, 2013)
The aim of this journal article is to offer a paradigmatic analysis of the formation of adjectives by means of affixation in Old English. More specifically, the focus is on the change of meaning attributable to the processes of word-formation that turn out affixal adjectives. In a paradigmatic model, the formal modification of stems maps onto semantic and/or syntactic modifications, which are couched in terms of semantic and syntactic rules. After an analysis of the semantic and syntactic rules that apply in the formation of 3,365 derived adjectives, two conclusions are reached. In the first place, 19 prefixes out of 56 perform one derivational function, as opposed to 21 suffixes out of a total of 51, which means that the degree of polysemy displayed by prefixes is slightly higher than that of suffixes. Secondly, only two derivational functions are realized by one affix, which also shows that a one-to-one correspondence between affixes and derivational functions is the exception rather than the rule.